SPECTRAL SIGNATURE IDENTIFICATION OF LAND COVER IN FADAK FARM /KARBALA GOVERNORATE AND EVALUATION OF ITS SUITABILITY FOR DATE PALM CULTIVATION - Taha, K. M.; Hamad, A. I. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The study aims to evaluate the lands of Fadak Farm and their suitability for palm trees cultivation. An area of 2,000 dunams was selected as the study site .It is located in Karbala Governorate between longitudes 43°51’44" and 43°35’16" E and latitudes 32°43’56" and 32°42’59" N. Sentinel-2A satellite imagery was used, Two pedons were identified—one in a cultivated area and the other in an uncultivated -with 40 surface soil samples collected. These samples were analyzed in the laboratory.The spectral signature of the existing land cover in the farm was determined. The reflectance values for date palm trees were 5252 in the green band, 4440 in the red band, and 6280 in the near-infrared band, covering 12% of the surface area. Newly planted date palms had reflectance values of 4708(green), 5196(red), and 6160 (near-infrared), covering 25% of the area. Barren lands covered 43% of the area, with reflectance values of 4804, 5700, and 6180 in the green, red, and near-infrared bands, respectively. Water bodies showed reflectance values of 1349 (blue), 1534 (green), 1532 (red), and 1830 (near-infrared), covering 10% of the area. Built-up areas also covered 10%, with reflectance values of 8504, 7468, and 6904 for the green, red, and near-infrared bands, respectively .The results indicated that all the covers in Fadak Farm showed the highest reflectance in the near-infrared band. The results showed two levels of suitability for date palm cultivation: moderately suitable S2 and marginally suitable S3 .